Analysis of a resistance force for the locked-wheel of push-pull locomotion rovers using large subsidence. (April 2021) - Fujiwara, Daisuke; Tsujikawa, Naoki; Oshima, Tetsuya; Iizuka, Kojiro
Highlights: Investigation of locked wheel-soil interaction for Push-Pull Locomotion. Resistance force at different wheel and sinkage conditions. Considering resistance force of locked-wheel theoretically. Abstract: This paper provides a quantitative analysis of the resistance force of the locked-wheel for push-pull locomotion rovers using intentional sinkage. Our previous study has confirmed that push-pull locomotion using intentional subsidence at an initial position can contribute to improving the traveling performance. The key factor of this scheme is the resistance force of the locked-wheel. However, the resistance force at different sinkage conditions and wheel sizes (e.g., mass, width, and diameter) remains unclear, especially for the individual locked-wheel. The detailed investigation of this interaction can contribute to the accurate estimation of rover mobility. This paper, therefore, investigates the locked-wheel and soil interaction at different sinkage conditions experimentally, especially focusing on the intentional sinkage condition. Additionally, the resistance force is considered theoretically through the knowledge based on the soil flow patterns beneath the locked-wheel. The experimental results confirmed that the resistance force of the locked-wheel rose as the initial sinkage, wheel size, and weight increases. Furthermore, the theoretical calculation suggested the resistance force increased with a similar tendency of the experimental data.